Experimental study on uniaxial compression after creep characteristics of similar soft rock containing cross cracks. Issue 1 (January 2021) - Cui, Lizhuang; Ge, Qiang; Zhou, Tongtong; Liu, Yaqi; Wang, Yongyan
Abstract: In order to study the creep phenomenon and failure law of rock materials containing cracks, uniaxial compression test and uniaxial compression test after creep are carried out on similar soft rock samples containing different angles of cross cracks, and the differences of rock mechanical properties after two tests are compared and analyzed. Results show that creep effect increases the compactness of the internal structure of the sample, the elastic modulus improve, enhance the ability of resistance to elastic deformation, the peak strength increases, and 15° cross crack sample is more seriously damaged, 30°, 45° and 60° cross crack samples generate deeper and longer crack propagation and broken degree is lower, 75° and cross sample produce fewer cracks.